Bahasa sebagai Media Komunikasi Dakwah - Rumra, Moh. Yamin; Hakis, Hakis (Jurnal Ilmu Komunikasi, 2023)
Language is a powerful means that communicators can use to convey the messages. This research aims to examine the role of language as a medium in da’wah communication. Using library research with a critical discourse analysis approach, the research results show that; 1). Language is one of the most effective communication media for carrying out da’wah communication, which has the main roles, namely labeling, interaction, and information transmission, 2). Language is a very vital medium to convey da’wah communication messages; so within holy Qur’an there are many words found such as "qaulan" that need to be paid attention to by communicators. The word "qaulan" is always paired with wise words, such as layyinan, makruf, tsaqilah, karimah, sadidah, balighah, maisyuroh, which means that the Muslim preachers must be role models for adherents in using language.